Efficacy of 3D-printed patient specific implant for orbital wall fracture repair in a series of 40 patients - Min Kyu Yang; Seong Jung Ha; Gye Jung Kim; Junhyeok Ock; Namkug Kim; Ho-Seok Sa (Scientific Reports)
Abstract This study was aimed to evaluate the efficacy of a 3D-printed patient specific implant (PSI) made of polycaprolactone (PCL) in repairing orbital wall fractures. We retrospectively reviewed patients who underwent surgical repair for unilateral orbital wall fractures using a 3D-printed PCL PSI. Computed tomography scans were used to compare the orbital tissue volumes and the morphological similarity (root-mean-square [RMS] conformance distance) between the fractured wall and the mirrored counterpart before and after surgery. All orbital fractures (inferior wall, 19; medial wall, 9; and combined inferior and medial walls, 12) were successfully repaired without postoperative complications. The mean time for implant insertion during surgery was 19.8 s (range, 3–60). The mean orbital tissue volume ratio between the fractured orbit and the contralateral normal orbit significantly decreased after surgery (109.0% preoperatively vs. 100.6% at postoperative 6 months, P < 0.001, paired t-test). The median RMS conformance distance significantly decreased after surgery (3.426 mm preoperatively vs. 1.073 mm at postoperative 6 months, P < 0.001, Wilcoxon signed-rank test). Our findings suggest that using a 3D-printed PCL PSI could effectively restore the original volume and shape of the orbit, thus being a valuable addition to the surgeon’s armamentarium for managing orbital wall fractures.